On the nature of medieval song: the declamation of plainchant and the lyric structure of the fourteenth-century motet - Clarkson, George Austin Elliot (Michigan University microfilms international, 1980)
Submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy, in the Faculty, Columbia University